Synthesis and Phase Stability Study of Some Equiatomic High Entropy Alloys - Pandey, Vivek Kumar (IIT(BHU) Varanasi, 2021)
Abstract is available in content.
Keywords: Synthesis and Phase Stability; Study of Some Equiatomic; High Entropy Alloys